(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article provides a philosophical and methodological analysis of the relationship between Islam and the phenomenon of radicalization in the context of globalization. It substantiates the fundamental ontological distinction between Islam as a normative value-based religious system and extremism as a form of political violence. The study argues that reducing a complex religious-civilizational tradition to manifestations of terrorism is conceptually flawed and largely shaped by geopolitical and modernization processes.